2016
DOI: 10.1002/aenm.201601116
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Stable Perovskite Solar Cells based on a Low‐Cost Carbon Cloth

Abstract: A low‐cost carbon cloth is applied in perovskite solar cells (PSC) as a collector composite and degradation inhibitor. This study incorporates carbon fibers as a back contact in perovskite solar cells, which results in enhancement in all photovoltaic parameters. This material is suitable for large‐scale fabrication of PSCs as it has shown an improved long‐term stability when compared to the gold counterpart under elevated temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 42 publications
(45 reference statements)
1
69
0
Order By: Relevance
“…Carbon cloth and carbon fibers, widely used in DSSCs and batteries, replaced gold in a batch of PSCs proposed by Gholipour et al 330 The optimized device configuration led to a PCE of 14.8%. Long-term stability was studied under a N 2 atmosphere, 85 1C, constant 1 sun illumination and MPP tracking.…”
Section: Stability Of Carbon-based Pscsmentioning
confidence: 98%
“…Carbon cloth and carbon fibers, widely used in DSSCs and batteries, replaced gold in a batch of PSCs proposed by Gholipour et al 330 The optimized device configuration led to a PCE of 14.8%. Long-term stability was studied under a N 2 atmosphere, 85 1C, constant 1 sun illumination and MPP tracking.…”
Section: Stability Of Carbon-based Pscsmentioning
confidence: 98%
“…However, Gholipour et al. reported the use of carbon cloth as back‐contact in PSCs . In brief, by embedding the carbon cloth in a carbon paste, the devices retained more than half of their initial PCE (≈15 %) under full illumination after over 100 h, compared to less than 20 % in just 20 h for the gold controls, when exposed to thermal stress (85 °C).…”
Section: Back‐electrodes: Beyond Gold and Towards Printable Inksmentioning
confidence: 99%
“…However,G holipour et al reported the use of carbon cloth as back-contacti n PSCs. [57] In brief, by embedding the carbon cloth in ac arbon paste,t he devices retained more than half of their initial PCE ( % 15 %) under full illumination after over 100 h, compared to less than 20 %i nj ust 20 hf or the gold controls, when exposed to thermals tress (85 8C). Aitola et al also found similarp erformance and resilience to heat by using press-transferred single-walled carbonn anotube films infiltrated with spiro-OMeTAD.…”
Section: Back-electrodes:beyond Gold and Towards Printable Inksmentioning
confidence: 99%
“…Thus, lots of efforts have been paid to develop alternative ETL materials to TiO 2 , among which SnO 2 is an especially promising candidate, owing to the larger bandgap (3.8 eV) which makes the material less sensitive to UV illumination and the higher electron mobility (up to 240 cm 2 V −1 s −1 ) and deeper CBM (conduction band minimum) which enhance the photogenerated carrier collection efficiency of PSCs. Fang and co‐workers reported in 2015 a low‐temperature solution‐processed SnO 2 layer as ETL of PSCs, achieving a PCE of 17.2%, and thence SnO 2 ETL attracted more and more attentions, and rapid progresses have been made in PSCs with SnO 2 ETL and recently an impressive certified record efficiency of more than 23% has been achieved by You group with nanoparticle SnO 2 as planar ETL of PSCs . However, the current successes in the SnO 2 application are still restricted to the planar SnO 2 (p‐SnO 2 ) structure.…”
Section: Introductionmentioning
confidence: 99%